Correlation between IL-8, IL-6 in tonsillitis patients and progressive of disease - Faihan, Wijdan Abdulameer; Darweesh, Mayyada F.; Zwamel, Ahmed H. (International Journal of Psychosocial Rehabilitation, 2020)
Tonsil is the organ of the first line of host defense against pathogenic agents, but also a place with recurrent chronic inflammatory processes. It represents the effectors of systemic humoral and cellular immunity .So this study aimed to evaluate IL-8, IL_6 serum level in different types of tonsillitis and their correlation with development of disease. This study included 100 patients attending to Al-Sadder Medical city in ENT unit in Najaf governorate .The patients were classified into two groups: seventy patients with tonsillitis who were subdivided into acute tonsillitis, chronic tonsillitis and recurrent tonsillitis as well as thirty patients with tonsillectomy. Five ml of a venous blood sample was collected from each patient and control 2ml of blood put in EDTA tube for total and differential blood count and 3ml for ELISA testing to determine the level of IL-8 and IL-6. This study has shown that higher frequency of tonsillitis in males (52.9%). The highest percentage of patients appeared with Grade 3 (33.6%), followed by Grade 2 (22.7%) in tonsillitis patients and grade 4(43.4%), grade 3(33.3%) in tonsillectomy patients. The level of IL-8, IL-6 was higher in tonsillitis patients and tonsillectomy than in healthy subjects. IL-8, IL-6 serum level was highly increased among the patients in grade 3, 4 (46.57, 50.65 pg/ml for IL-8 and 45.65 ± 5.61, 70 ± 4.32 pg/ml for IL-6 ) and highly significant increase in chronic and recurrent patients (28.87, 26.94 for IL-8) and (31.74, 29.54 for IL-6). In conclusion there is a strong correlation between IL-6 and IL-8, furthermore, IL-8 strongly correlate with Monocyte count. IL-6 and IL-8 found to be increase along with tonsillitis severity i.e. the grade 3, 4 tonsillitis have high level of IL-6 and IL-8.